Manufacturing system analysis to improve performance using modeling and simulation - Ang, Thomas Kok Peng (2018)
This project aims to study the production line through simulation modelling and analysis to improve the performance of a production line. Experiments on various condition of the shop floor will be conducted and methods for overall improvement in the throughput will be derived thereafter. The author’s Industrial Attachment (IA) experience at an aerospace manufacturing component company will be the foundation set for this project. All the data collected will serve as an actual case study which enables the author to expand his production control knowledge gained during his time in the company. Literature review of precedents or prior work assignments was done on analysis methods of re-entrant production line, performance indicators and benefits of simulation in today’s industry. The author linearized the re-entrant production line and the actual operating performance of the line was identified. A simulation model was built, verified and validated, using a simulation software, SIMUL8. Experiments was conducted on the model with varying parameters, such as, breakdown time, input distribution, increase machine capability, operating hours. The experiments yielded an increase in the overall throughput. Finally, proposed recommendations to the production line for improvement in the throughput value will be suggested.